The Representation Of American Manhood Reflected InChristoper Nolan's Batman The Dark Knight Rises Movie (2012): A Sociological Approach. - Sintowati, Eka Pratiwi; , Dr. Phil Dewi Candraningrum, S.Pd, M.Ed; , Drs. Abdillah Nugroho, M.Hum (2013)
The major problem in this study is how the representation of American Manhood reflected in Christopher Nolan‟s Batman the Dark Knight Rises movie. The purposes of the study are analyzing the structural elements and American background of the American society based on the sociological approach. This study belongs to the qualitative study. In this method, the writer uses two data sources; they are primary and secondary data sources. The primary data source is the movie, Batman the Dark Knight Rises it self. Meanwhile the secondary one are Swingewood‟s sociological and any other data relates to this study. The object of the study is Christopher Nolan‟s Batman the dark Knight Rises movie. In this research there are five the techniques of collecting data, they are; watching the movie, taking notes of important parts, arranging the data, selecting the important parts and the last is making the selecting materials into a good unity. In analyzing the data, the researcher uses descriptive analysis. Results of the research shows the following two conclusions based on structural elements of the Batman the Dark Knight Rises movie and sociological analysis. First, the relation between the structural elements and the movie is tied each other. Second, in Batman the Dark Knight Rises movie Christopher Nolan wants to show through this movie that American manhood of Bruce Wayne as the Major character in this movie has made the all of aspects life in America is back to normally.